Mercer Subglacial Lake radiocarbon and stable isotope data - Rosenheim, Brad; Venturelli, Ryan (IEDA: US Antarctic Program Data Center, 2023)
This dataset includes radiocarbon (¹⁴C) and stable carbon isotope (δ¹³C) data for a sediment core from Mercer Subglacial Lake. In addition, this dataset includes ¹⁴C and δ¹³C for dissolved organic carbon, dissolved inorganic carbon, and particulate organic carbon from the Mercer Subglacial Lake water column.